P1004REDUCED ERYTHROCYTE LIFE SPAN IN PATIENTS WITH TYPE 2 DIABETES UNDERGOING LONG-TERM HAEMODIALYSIS. (6th June 2020) - Bomholt, Tobias; Oturai, Peter; Rix, Marianne; Feldt-Rasmussen, Bo; Hornum, Mads
Abstract: Background and Aims: Anaemia in long-term haemodialysis (HD) is caused by reduced erythropoietin levels but shortened erythrocyte life span is thought to contribute. However, reduced erythrocyte life span has never been documented in patients with type 2 diabetes (T2D) undergoing long-term HD. The aim of the study was to establish if the erythrocyte life span is decreased in in patients with type 2 diabetes (T2D) undergoing long-term HD and to investigate predictors of reduced erythrocyte life span. Method: Patients with T2D undergoing long-term HD and patients with T2D without nephropathy (control group) (eGFR above 60ml/min) were included. Erythrocyte life span was measured using Chromium-51 ( 51 Cr) labelled erythrocytes. Blood radiotracer activity was measured 6-8 times over 3-5 weeks to calculate the erythrocyte half-life for each patient. Markers for haemolysis, blood pressure and time spend in dialysis were obtained 5 times over 16 weeks and correlated to the erythrocyte half-life. Results: For patients with T2D undergoing HD (n=13), the median half-life was 34.5 days (30.6 - 40.7) compared with 44.6 days (43.5 - 58.0) in the control group (n=10) corresponding to a 23 % difference (p=0.0003). From the half-life, the median erythrocyte life span was estimated to 49.7 days (44.1-58.6) and 64.2 days (62.6-83.5), respectively. For patients with T2D undergoing HD no correlation was found between the erythrocyte half-life and markers of haemolysis, blood pressure or time spend in dialysis. Conclusion: The half-life of erythrocytes was reduced by 23 % in patients with T2D undergoing long-term HD compared with a control group. This reflects that erythrocyte life span is reduced in these patients. No specific markers of haemolysis could be correlated to the findings.